Medical Ethics: Understanding, Teaching and Practice - Khan, M Iqbal (International Journal of Pathology, 2018)
Ethics is a word derived from the Greek ‘ethikos’ whichmeans a study of the principles of living. Ethics nowhas become to mean ‘a set of rules or standardsgoverning the conduct of a person or the members of aprofession’. Medical Ethics deals with the moralprinciples that medics should follow in theirprofessional life. The scope of medical ethics is wideand inclusive of developing codes and guidelines,promoting ethical practices and preventing ethicalbreaches. It also includes the physicians’ relationshipwith patients, colleagues, members of the relatedindustry, and at large, the society and the nation or thestate. Ethical environment pays in terms of goodstandards, fine practices and special care byphysicians. Essential elements of this environment areprofessional competence, good collegial and patientrelationship along with compliance of otherprofessional and ethical obligations.Fast-moving societal and technological changes in the21st century are restructuring the Health profession.These drifts will have a particular impact on thepreparation of health care professionals, especiallyphysicians. The volume of medical knowledge isincreasing. The range and complexity of treatmentoptions are widening. At the same time, communityrequirements and expectations from physicians havebeen amplified. To meet these rising demands, healthcare professionals must learn the skills to criticallyanalyze new developments, keep abreast with thedevelopments of their field, practice on the basis of thebest evidence available and be able to explain andjustify their advice to patients. Apart from acquiringknowledge and skills, proper morals, dedication,altruism, and sympathy without discrimination arecrucial components of a medic’s life.